Manual de procedimientos para agentes de aduana que realizan desaduanización de gases medicinales aplicando el régimen de admisión temporal para perfeccionamiento activo régimen 21 - Lozano Arias, Yomira Katherine (2019)
The present work was based on the design of a manual of procedures for customs agents who perform the customs clearance of medical gases applying the Temporary Admission Regime for Active Improvement (Regime 21). In this case, although in Ecuador and particularly in the city of Guayaquil there are several agencies that provide the customs agency service, only some of them offer the service to companies that are dedicated to the importation of medical gases. In this area, the problem of study is presented, mainly associated with the delays in delivery dates agreed with the customers of the imported gases; this attributed to the different processes that must be executed for the nationalization of the merchandise……